Induced Breeding of Fresh Water Menoda Catfish (Hemibagrus Menoda) Using Ovupin Hormone (Journal of Biodiversity Conservation and Bioresource Management, 2021)
An experiment on induced breeding of menoda catfish, Hemibagrus menoda was conducted during the period from May 2017 to July 2018 by using commercial Ovupin hormone (GnRHa, Gonadotropin Releasing Hormone Analogues) to attain its optimum dose. The study consists of three treatments, each with three replications. The objective of the experiment was to find out the effective dose for induced breeding. The breeding parameters were determined in terms of ovulation, fertilization, hatching, and survival rate. A total of 36 males and 18 females lived brood fish were kept in the ratio of 2♂:1♀ for breeding purpose. The commercial Ovupin hormone were injected at the doses of 4 (T1), 6 (T2), 7 (T3) mL Ovupin·kg-1body weight for female and 1.5(T1), 2 (T2), 3(T3) mL Ovupin·kg-1 body weight for male in a triplicate replication. In this study, it was found that treatment T2 demonstrated the best spawning performance for both male and female and were statistically significant (p